TREATMENT OF OVARIAN ENDOMETRIOMA ACCORDING TO THE CLINICAL STAGE - Munkhbayar , Ch.; Amarjargal , O.; Munkhbayarlakh , S.; Yanjinsuren , D. (EurasianUnionScientists, 2020)
Endometriosis is a chronic disease in which the glandular and connective tissues in the lining of the uterus migrate to tissues and organs other than the uterus, causing inflammatory infiltration and adhesions in the area, leading to chronic pelvic pain, infertility and disability to work. The aim of this study is diagnosing and treating ovarian endometrioma depending on its clinical stage and conducting a comparative study of the treatment results.